Photovoltaic performance of P3HT: SWCNT: PCBM based bulk heterojunction solar cell - Khan, Saad Mohammed; Hasan, Ajnan Aron; Saha, Avizet (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.